In vitro reconstitution of mammalian U2 and U5 snRNPs active in splicing: Sm proteins are functionally interchangeable and are essential for the formation of functional U2 and U5 snRNPs. - Ségault, V (1995)
An in vitro reconstitution/splicing complementation system has been developed which has allowed the investigation of the role of mammalian U2 and U5 snRNP components in splicing. U2 or U5 snRNP cores are first reconstituted from purified native snRNP core proteins and snRNA in the absence of cellular extract and are subsequently added to splicing extracts depleted of either U2 or U5 snRNP. When snRNPs reconstituted with HeLa U2 or U5 snRNA were added to U2- or U5-depleted nuclear extract, splicing was complemented. Addition of naked snRNA, on the other hand, did not restore splicing, demonstrating that the core proteins are essential for both U2 and U5 snRNP functions in splicing. Hybrid U2 or U5 snRNPs, reconstituted with core proteins isolated from U1 or U2 snRNPs, were equally active in splicing complementation, indicating that the snRNP core proteins are functionally interchangeable. U5 snRNPs reconstituted from in vitro transcribed U5 snRNA restored splicing to a level identical to that observed with particles reconstituted from authentic HeLa U5 snRNA. In contrast, splicing could not be restored to U2-depleted extract by the addition of snRNPs reconstituted from synthetic U2 snRNA, suggesting that U2 snRNA base modifications are essential for U2 snRNP function.